2010
DOI: 10.1007/s00586-010-1520-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of diffusion magnetic resonance imaging of the lumbar foraminal nerve root entrapment

Abstract: Diffusion-weighted imaging (DWI) can provide valuable structural information about tissues that may be useful for clinical applications in evaluating lumbar foraminal nerve root entrapment. Our purpose was to visualize the lumbar nerve root and to analyze its morphology, and to measure its apparent diffusion coefficient (ADC) in healthy volunteers and patients with lumbar foraminal stenosis using 1.5-T magnetic resonance imaging. Fourteen patients with lumbar foraminal stenosis and 14 healthy volunteers were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 35 publications
(42 reference statements)
3
52
1
1
Order By: Relevance
“…MR neurography by using DWI can clearly show lumbar nerve roots, and the mean ADC in nerve root entrapment with foraminal stenosis is higher than in intact nerve roots in approximately a 10-minute scan time by using MR imaging at 1.5 T. 20 The ADC map is limited because the tissue contrast between nerves and surrounding tissues is poor. 15 In this study, we have shown that DTI can clearly show tractograms of lumbar nerve roots and determine FA values of the nerve roots in patients and healthy volunteers in approximately a 5-minute scan time by using MR imaging at 3T.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR neurography by using DWI can clearly show lumbar nerve roots, and the mean ADC in nerve root entrapment with foraminal stenosis is higher than in intact nerve roots in approximately a 10-minute scan time by using MR imaging at 1.5 T. 20 The ADC map is limited because the tissue contrast between nerves and surrounding tissues is poor. 15 In this study, we have shown that DTI can clearly show tractograms of lumbar nerve roots and determine FA values of the nerve roots in patients and healthy volunteers in approximately a 5-minute scan time by using MR imaging at 3T.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Imaging of the spinal cord is challenging because of technical limitations such as the relatively small size of the cord, susceptibility artifacts because of tissue-bone interfaces, and the motion artifacts arising from respiratory activity. 19 Although we reported previously that DWI of lumbar nerves by using 1.5T MR imaging could visualize and quantitatively evaluate lumbar nerve entrapment with foraminal stenosis, 20 to date, quantitative DTI has not been applied to evaluate the pathology of lumbar nerve root entrapment. Nerve root entrapment may contribute to radicular symptoms in patients with lumbar foraminal stenosis.…”
mentioning
confidence: 99%
“…Mean apparent diffusion coefficient values are higher in compressed spinal nerve roots compared with intact nerve roots. 22 This suggests demyelination and edema (restrictive diffusion). 22 The DWI technique promises a noninvasive diagnostic assessment of early changes associated with degenerative compression of spinal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…22 This suggests demyelination and edema (restrictive diffusion). 22 The DWI technique promises a noninvasive diagnostic assessment of early changes associated with degenerative compression of spinal nerves. 23 Our patient presented with acute low back pain, and the diagnosis was CLDCS.…”
Section: Discussionmentioning
confidence: 99%
“…For this aim, it is necessary to include in the acquisition a low b value, usually ranging between 0 to 50 s/mm 2 . ADC may help to confirm and quantify the presence of edema in PN trauma or compression (11) and characterize tumoral lesions (12). DWN allows an accurate anatomical representation of PN by means of a fast and easy post process.…”
Section: Dwi Neurographymentioning
confidence: 99%